High Homogenization Speeds for Preparing Unstable Myofibrillar Protein–Olive Oil Emulsions. Issue 5 (22nd April 2019) - Li, Ruren; He, Qing; Rong, Liangyan; Lin, Yanting; Jia, Na; Shao, Junhua; Liu, Dengyong
Abstract: Natural protein‐based oil‐in‐water emulsions have recently attracted a lot of attention because of their potential as a synthetic emulsifier replacer. It is, however, unclear how the emulsification process and protein concentration may affect the stability of such emulsions. Therefore, this study investigated the effects of homogenization speeds (4, 000, 8, 000, 12, 000, and 16, 000 rpm/min) and myofibrillar protein (MP) concentrations (10, 20, 30, 40, and 50 mg/mL) on the stability of MP–olive oil emulsion. The emulsifying creaming index, emulsifying activity index (EAI), droplet size, microstructure, free sulfhydryl content, and zeta potential of the emulsion were measured. The results showed that with the condition of sufficient emulsifier (at least 20 mg/mL), the EAI increased, and the droplet size and zeta potential of emulsions decreased with the increase of homogenization speed. Emulsions were stable at 4, 000 and 8, 000 rpm/min (20, 30, 40, and 50 mg/mL) within 48 hr, and they were unstable at 12, 000 and 16, 000 rpm/min (20, 30, 40, and 50 mg/mL) within 48 hr. This result is mainly attributed to the fact that sulfhydryl–disulfide interchange leads the excessive aggregate of MP at the oil–water interface. Practical Application: Myofibrillar protein–olive oil emulsions (oil‐in‐water) may be used to deliver nutrients into food products. In this study, myofibrillar protein–olive oil emulsions stabilized with the optimizing emulsification conditions. This study may have important implications to produce food‐grade myofibrillar protein–olive oil emulsions to deliver nutrients.